The Influence of Intellectual Ability on Lecturers' Performance and Competencies - Mochammad Munir Rachman; Ch . Menuk Sri Handayani; Sugijanto Sugijanto (Journal of Theoretical and Applied Management (Jurnal Manajemen Teori dan Terapan), 2022)
Objective: The main objective of this study is to analyze the importance of intellectual abilities in increasing the role of competence and strengthening the performance of lecturers in the management study program at a private university in Surabaya. Design/Methods/Approach: The study utilizes 200 samples obtained by distributing questionnaires to respondents. The explanatory method makes it possible to measure confirmatory factor analysis and SEM analysis to test the model.  Finding: The results indicate that intellectual ability has a significant effect on lecturer competence and indirect positive effect on performance. However, the indirect effect is less strong than its direct effect on performance. These results indicate that they have a logical, inspirational, creative, and innovative mindset in carrying out the "tri dharma”, such as education, producing scientific papers published in reputable national and international journals, publishing the results of community service, and contributing to other activities. In short, the stronger the professional competence, the higher the successful performance achieved because of the contribution of intellectual ability as an independent domain of lecturers. Originality: This is the first comprehensive study conducted at the 18 private universities in Indonesia. Therefore, it will be valuable to better understand the intellectual abilities of lecturers and improve the relationship between their performance and competence. Practical/Policy implication (optional): The success of lecturers in "tri dharma” activities is an important policy for the academic community, that characterized by their success in producing high performance, not only for individual but also for the universities. In addition, the study concludes with a location model that can be used as an important tool by university leaders in conducting their national and international business because this model can also be applied in various sectors other than the higher education sector.